Upaya Rumah Genah Adhiyaksa Kejaksaan Negeri Gianyar Dalam Menekan Tingkat Kejahatan Di Wilayah Kejaksaan Negeri Gianyar - Egya Ridhona Tarigan; I Dewa Gede Dana Sugama (KOLONI, 2024)
The Attorney General's Office is an institution that plays an important role in law enforcement in Indonesia, it is also an institution that can provide a sense of justice for people who commit crimes. In this journal, the issue raised is how the Genah Adhyaksa house or the Restorative Justice house can provide principles of justice for perpetrators of crimes and can reduce crime rates, especially in the area of the Gianyar District Attorney's Office. The purpose of writing this journal is to find out how the crime rate existed in the Gianyar district attorney's office before and after the existence of the Genah Adhyaksa House or the Restorative Justice House, whether it increased, according to, or was static. The research method used is the empirical research method. The results of this study are that the crime rate in the Gianyar District Prosecutor's Office has decreased slightly when compared to previous years before the existence of the Genah Adhyaksa Restorative justice house. However, until this writing was written, the crime rate at the Gianyar State Prosecutor's Office was still quite high because these crimes arise from the personal conscience of the person who committed the crime. The progress of Justice Genah Adhyaksa's Restorative House can be seen on the official website of the Gianyar State Attorney's Office.